PENGARUH KOMPETENSI, GAYA KEPEMIMPINAN, DAN PELATIHAN TERHADAP KINERJA GURU DI SMPN 1 JEMBER JAWA TIMUR - Febriandika, Triyan; Handoko, Yunus; Rachmawati, Ike Kusdyah (Universitas Nusa Cendana, 2024)
The quality of a school is reflected in teacher performance, which significantly impacts overall education quality. Teacher performance is the outcome of tasks performed based on skills, experience, commitment, and time management. Assessing this performance is crucial for identifying obstacles and rectifying errors to achieve learning goals. At SMPN 1 Jember, teacher performance is commendable, meeting 80% of the school target, yet teachers often struggle with administrative duties, which can detract from classroom focus. This study aims to determine whether competence, leadership style, and training individually and collectively influence teacher performance at SMPN 1 Jember. Using multiple linear regression with SPSS 29 software, the research employs a saturated sampling method, involving all 48 teachers at SMPN 1 Jember. Findings indicate that competence and leadership style positively and significantly impact teacher performance, while training has a negative yet significant effect. Collectively, competence, leadership style, and training positively and significantly influence teacher performance at SMPN 1 Jember. Keywords: Teacher Performance; Competence; Leadership Style; Training